2005
DOI: 10.1021/ja045331g
|View full text |Cite
|
Sign up to set email alerts
|

Nonclassical Crystallization:  Mesocrystals and Morphology Change of CaCO3 Crystals in the Presence of a Polyelectrolyte Additive

Abstract: Crystallization of calcite from differently concentrated calcium chloride solutions by the CO2 gas diffusion technique in the presence of polystyrene sulfonate yields crystal superstructures with unusual morphology. From the typical calcite rhombohedra as a starting situation, the morphology can be systematically varied via rounded edges and truncated triangles to finally concavely bended lens-like superstructures. Although these "crystals" are apparently well-faceted in light microscopy, electron microscopy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
386
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 389 publications
(414 citation statements)
references
References 30 publications
23
386
1
4
Order By: Relevance
“…The size at which an additive begins to affect the morphology of calcite depends on the additive binding strength, the concentration, and the supersaturation, which was rationalized by considering additive binding to available kink sites. Our data also confirm that calcite grows by a classical ion‐by‐ion mechanism in the presence of PSS18 rather than a non‐classical assembly of nanoparticles 27. These results provide insight into the growth mechanisms of sparingly soluble crystals such as calcite, and show that it is important to consider the action of additives on nucleation and growth to obtain product crystals with the desired properties.…”
supporting
confidence: 71%
“…The size at which an additive begins to affect the morphology of calcite depends on the additive binding strength, the concentration, and the supersaturation, which was rationalized by considering additive binding to available kink sites. Our data also confirm that calcite grows by a classical ion‐by‐ion mechanism in the presence of PSS18 rather than a non‐classical assembly of nanoparticles 27. These results provide insight into the growth mechanisms of sparingly soluble crystals such as calcite, and show that it is important to consider the action of additives on nucleation and growth to obtain product crystals with the desired properties.…”
supporting
confidence: 71%
“…The mineralisation was performed by a slow CO2 gas diffusion technique as described in our previous papers. 43), 44) To investigate the effect of added polymer, crystallizations were performed in the presence of different concentrations of polymer and CaCl2 in glass bottles with glass slides, which were put into the same closed desiccator at room temperature. All glassware including glass bottles and small pieces of glass substrates were cleaned as follows: firstly sonicated in ethanol, then rinsed with distilled water, further soaked with a H2O-HNO3 (65%)-H2O2 (1:1:1, v/v/v) solution, then rinsed with doubly distilled H2O, and finally dried at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…42) Despite the rapidly increasing number of observations of mesocrystals, relatively little is yet known about their formation mechanism. In a series of papers 43)- 45) we demonstrated that addition of a simple polyelectrolyte as poly (styrene sulfonate) can modify the crystal growth of calcium carbonate in a manifold fashion leading to nanocrystal superstructures with astonishing complexity. The remarkable change from the typical single crystal calcite rhombohedron with (104) faces to mesocrystals presenting their unusual {001} faces with additional rounded edges was outlined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, mesocrystal formation has been reported for a wide range of materials, including biominerals 16,17 (e.g. sea urchins 18 and hydroxyapatite 19,20 ) and metal complexes (e.g.…”
Section: Introductionmentioning
confidence: 99%